Lactational exposure to hydroxylated polychlorinated biphenyl (OH‐PCB 106) causes hyperactivity in male rat pups by aberrant increase in dopamine and its receptor. Issue 8 (20th September 2012) - Lesmana, Ronny; Shimokawa, Noriaki; Takatsuru, Yusuke; Iwasaki, Toshiharu; Koibuchi, Noriyuki
<x xml:space="preserve">Abstract</x> Polychlorinated biphenyls (PCBs) are recognized as persistent environmental pollutants that may cause adverse health problems. Despite extensive investigations of PCB in neural function, little is known about behavioral traits by PCB exposure and its neurochemical mechanism. Here, we report the behavioral study of a rat pup that was exposed to hydroxylated‐PCB 106 (OH‐PCB 106; 4‐hydroxy‐2', 3, 3', 4', 5'‐pentachlorobiphenyl) through maternal milk. The different groups of mothers received via gavage corn oil vehicle, 0.5, 5, or 50 mg/kg body weight of OH‐PCB 106 every second day from day 3 to 13 after delivery. The exposure did not affect the body weight of the dams or the physical development of the newborn pups in both sexes. Male rats exposed to OH‐PCB 106 showed hyperactivity that was characterized by increased locomotor activity in novel environment and circadian period. Interestingly, OH‐PCB 106‐exposed rat pups displayed abnormally high levels of dopamine and D2 dopamine receptor (D2DR), but not D1DR and D5DR, in the striatum, an important center for the coordination of behavior. These findings indicate that OH‐PCB 106 has a significant neurotoxic effect on rat behavior, which may be associated with increased D2DR mediated signals. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 876–883, 2014.